UPAYA PEMASARAN PARIWISATA PONOROGO MELALUI CITY BRANDING DALAM MENINGKATKAN KUNJUNGAN WISATAWAN (Studi Kasus pada City Branding Kabupaten Ponorogo dengan Tagline “Ethnic Art of Java - Widiana Puji Astuti; Andriani Kusumawati (Jurnal Administrasi Bisnis, 2018)
This research is based on the fact that Ponorogo Regency as a area that dominant with its local culture starting to implement city branding strategy since 2015 by use the cultural side especially art as a brand. This research is intended to explain (1) city branding process, (2) city branding hexagon implementation analysis , (3) impacts of city branding, and (4) barriers of city branding.The results of this research is city branding Ponorogo through the process of planning, study related potential of Ponorogo which then produces logo and tagline "Ethnic Art of Java", preparation of Human Resources (SDM) and tourist destinations. The most dominant component in city branding hexagon Ponorogo Regency is the people and the lowest is the prerequisite. The impact of city are on the quality of tourism and the quantity of tourist visits but there are some barriers from internal and external of organization on city branding Ponorogo implementation. Based on the results of this research, DISPAPORA have to evaluates and review city branding Ponorogo strategy again by involving potential parties such as goverment, artists, youth, and especially academics. Keywords: tourism marketing, city branding, tourist visit АBSTRАK Penelitian ini dilatar belakangi oleh adanya fakta bahwa Kabupaten Ponorogo sebagai daerah yang khas dengan budaya lokalnya mulai menerapkan strategi city branding sejak tahun 2015 dengan mengangkat sisi budaya khususnya kesenian sebagai brand. Pnelitian ini bertujuan untuk menjelaskan (1) proses city branding4) hambatan penerapan city branding.Hasil penelitian ini adalah Upaya city branding Ponorogo ini melalui proses perencanaan diantaranya penetapan tujuan, kajian terkait potensi Ponorogo yang kemudian menghasilkan logo dan tagline “Ethnic Art of Java”, mempersiapkan Sumber Daya Manusia (SDM) dan destinasi wisata. Komponen yang paling dominan dalam city branding hexagon Kabupaten Ponorogo adalah people dan yang terendah adalah prerequisite. City Branding Ponorogo berdampak terhadap kualitas pariwisata dan kuantitas kunjungan wisatawan namun dalam pelaksanaannya masih menemui beberapa kendala dari dalam dan luar organisasi. Berdasarkan hasil penelitian, sebaiknya DISPAPORA melakukan evaluasi dan mengkaji ulang strategi city branding Ponorogo dengan melibatkan pihak-pihak potensial seperti pemerintah, seniman, pemuda, dan khususnya akademisi. Kata kunci : pemasaran pariwisata, city branding, kunjungan wisatawan